Optimizing ploughing performance: The role of traction-control cylinder pressure on tractor wheel load - Jiří Čupera; Petr Porteš; František Bauer; Adam Polcar; Martin Fajman; Jan Henzl (Journal of Agriculture and Food Research)
This paper examines the impact of pressure change in the Traction-Control cylinder of a six-furrow semi-mounted reversible plough's on the vertical load distribution among the tractor's wheels. The study's findings indicate that increasing the pressure in the Traction-Control cylinder leads to a more balanced vertical load on the rear wheels of the tractor. This balance is achieved by transferring a portion of the plough's weight to the tractor's rear axle. The combined effect of the plough's weight, the vertical force exerted by its support wheel, and the ploughing forces creates a moment that equalizes the load between the in-furrow and on-land wheels. Adjusting the Traction-Control cylinder pressure significantly altered the lateral rear wheel load distribution, shifting the ratio from 60.8/39.2 to 51/49. Additionally, the Traction-Control cylinder's positive impact on fuel consumption and the overall performance of the ploughing set was demonstrated.